Opportunities and pitfalls for researchers to contribute to the design of evidence-based agricultural policies: lessons from Uganda - Pali, Pamela N.; Schut, Marc; Kibwika, P.; Wairegi, L.W.I.; Yami, M.; Asten, Piet J.A. van; Manyong, Victor M. (Informa UK Limited, 2018)
Agricultural policies in sub-Saharan Africa have paid insufficient attention to sustainable intensification. In Uganda, agricultural productivity has stagnated with aggregate increases in crop production being attributed to expansion of cultivated land area. To enhance sustainable crop intensification, the Ugandan Government collaborated with stakeholders to develop agricultural policies using an evidence-based approach. Previously, evidence-based decision-making tended to focus on the evidence base rather than evidence and its interactions within the broader policy context. We identify opportunities and pitfalls to strengthen science engagement in agricultural policy design by analysing the types of evidence required, and how it was shared and used during policy development. Qualitative tools captured stakeholders' perspectives of agricultural policies and their status in the policy cycle. Subsequent multi-level studies identified crop growth constraints and quantified yield gaps which were used to compute the economic analyses of policy options that subsequently contributed to sub-national program planning. The study identified a need to generate relevant evidence within a short time 'window' to influence policy design, power influence by different stakeholders and quality of stakeholder interaction. Opportunities for evidence integration surfaced at random phases of policy development due to researchers’ ’embededness’ within co-management and coordination structures.